2015
DOI: 10.4149/bll_2015_044
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between possible cytostatic and antiinflammatory potential of ketoprofen in the treatment of culture of colon and cervix cancer cell lines

Abstract: Summary. -In this study, a major part of genome of the pestivirus isolate 297 from Slovakia, comprising the 7195 nt-long 5΄-UTR-NS3 region was sequenced and analyzed. Conserved cleavage sites between individual viral proteins of this region were determined and the number of amino acids of respective proteins was estimated as follows: 168 for N pro , 100 for C, 227 for E rns , 195 for E1, 373 for E2, 70 for p7, 453 for NS2, and 683 for NS3. Based on sequence and phylogenetic analysis of 5΄-UTR, N pro , and E2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…45−47 However, a significant cytostatic effect was observed upon exposure of human cervical carcinoma (HeLa) and human colon cancer cells (Caco-2) to ketoprofen, which may be attributed to the NF-κB inhibition that was detected. 16…”
Section: Results and Discussionmentioning
confidence: 99%
“…45−47 However, a significant cytostatic effect was observed upon exposure of human cervical carcinoma (HeLa) and human colon cancer cells (Caco-2) to ketoprofen, which may be attributed to the NF-κB inhibition that was detected. 16…”
Section: Results and Discussionmentioning
confidence: 99%
“…One of the antiproliferative mechanisms of this drug is the transcription factor of NF-κB because NF-κB was evident at low doses of ketoprofen. Given that NF-κB is controlled by the modified expression of COX-2, the inhibition of this enzyme by ketoprofen is an important step in the treatment and prevention of colon and cervix cancer (25). Previous studies have accurately examined the effects of some NSAIDs in treating colon cancer, and their results indicated the importance of NSAIDs in the treatment and prevention of cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of epidemiological and experimental studies have revealed that prolonged treatment with non-steroidal anti-inflammatory drugs (NSAIDs), which are COX inhibitors, can reduce the risk of cancer (13). NSAIDs inhibit cell proliferation and induce apoptosis of a number of cancer cells in vitro and in vivo, which is considered to be an important mechanism for the anti-tumor and chemopreventive activity of NSAIDs (14). However, the molecular pathways of this process are still unclear.…”
Section: Introductionmentioning
confidence: 99%